Sparse representation based classification for face recognition - Lai, Jian (2015)
Building a computer as intelligent as or more intelligent than human is the ultimate goal of machine learning. To explore this powerful ability in computer vision, it inspires numerous interesting and useful research areas and applications. Face recognition (FR), as one of the most challenging problems in machine learning and computer vision, provides a good test bed to showhow intelligent amachine can be. Moreover, it shows huge potential for commercial and surveillance, such as access control, computer-human interaction and anti-terrorist. FR remains a hot research topic though it has been studied for more than three decades. One important reason is that there is still large gap between human and machine to recognize the identity of a face image due to extreme illumination, expression and pose variation, disguise, and occlusion et al..